Estelle Brodman and the first generation of library automation. - Peay WJ; Schoening P (Journal of the Medical Library Association, 2008)
OBJECTIVE: The purpose of this paper is to examine the contributions of Estelle Brodman, PhD, to the early application of computing technologies in health sciences libraries. METHODS: A review of the literature, oral histories, and materials contained in the archives of the Bernard Becker Medical Library at the Washington University School of Medicine was conducted. RESULTS: While the early computing technologies were not well suited to library applications, their exciting potential was recognized by visionaries like Dr. Brodman. The effective use of these technologies was made possible by creative and innovative projects and programs. The impact of these early efforts continues to resonate through library services and operations. CONCLUSIONS: Computing technologies have transformed libraries. Dr. Brodman's leadership in the early development and application of these technologies provided significant benefits to the health sciences library community.